Literature Review: Active Role of Husband in Care During Pregnancy - Litasari, Resna; Sunarni, Neli (Yayasan Inspirasi El Burhani, 2025)
Introduction: The husband's role in pregnancy care has a major influence on the health of the mother and fetus. Care during pregnancy is an important aspect to prevent complications and deaths that can occur during pregnancy and childbirth. Objective: This literature review aims to strengthen the understanding of the importance of husbands' active role in improving the quality of prenatal care and maternal health. Method: This study was conducted using the literature review method, the data source came from journals published in the last 10 years (2014-2024). Selection was made through screening titles, abstracts, and full text based on inclusion and exclusion criteria. Data were analyzed descriptively to identify the form of husband's involvement, factors that influence participation, and its impact on maternal and fetal health. Results: Analysis of 10 articles showed that husbands' involvement in antenatal care contributes positively to maternal and fetal health, including reducing maternal anxiety, increasing adherence to antenatal check-ups, and reducing the risk of complications. While factors such as education, culture, and busy work schedules influence the level of husband involvement, classes for pregnant women and educational programs for husbands effectively increase their awareness of their important role in pregnancy. Conclusions: The active role of husbands in pregnancy care has a significant positive impact on maternal and fetal health. Husband's involvement in emotional, physical, financial, and health access aspects plays an important role in improving the well-being of pregnant women.